(untitled) - Wells, Rosemary (New York, 1989)
Max and his sister Ruby go on an egg hunt and vie with each other for the prize--a chocolate chicken.
Keywords: Rabbits; Fiction; Brothers and sisters; Fiction; Easter; Fiction